Epizootology of Sheep Tizaniesiosis, Some Diagnostic Signs of the Causative Agent - Sh.Kh.Kurbanov; M.Ya.Hamzaeva (Zien Journals, 2022)
The article provides literature data on sheep thizaniezsiosis and its current epizootological state, according to individual studies, on sheep lesions with thizaniesiosis, anatomical and morphological symptoms of its pathogen, and differences from other intestinal cestodes
Keywords: cestodes; thizaniesia; scolex; strobila